2016
DOI: 10.1093/nutrit/nuw014
|View full text |Cite
|
Sign up to set email alerts
|

Potential misinterpretation of the nutritional value of dietary fiber: correcting fiber digestibility values for nondietary gut-interfering material

Abstract: The aim of this review is to identify the origin and implications of a nondietary material present in digesta and feces that interferes with the determination of dietary fiber in gastrointestinal contents. Negative values for ileal and fecal digestibility of dietary fiber are commonly reported in the literature for monogastric animal species, including humans. As negative values are not possible physiologically, this suggests the existence of a nondietary material in the gastrointestinal contents and feces tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 126 publications
0
32
0
Order By: Relevance
“…Results of several experiments also indicate low ileal digestibility values for dietary fibre in human ileostomates and ileal-cannulated pigs (11)(12)(13) . Montoya et al (14) discussed that non-dietary gut materials may interfere with dietary fibre determination in ileal digesta and thus lead to underestimation of dietary fibre ileal digestibility. For instance, an estimate of the ileal digestibility of soluble fibre in kiwifruit increased 50 % units when it was corrected for interfering non-dietary materials (15) .…”
mentioning
confidence: 99%
“…Results of several experiments also indicate low ileal digestibility values for dietary fibre in human ileostomates and ileal-cannulated pigs (11)(12)(13) . Montoya et al (14) discussed that non-dietary gut materials may interfere with dietary fibre determination in ileal digesta and thus lead to underestimation of dietary fibre ileal digestibility. For instance, an estimate of the ileal digestibility of soluble fibre in kiwifruit increased 50 % units when it was corrected for interfering non-dietary materials (15) .…”
mentioning
confidence: 99%
“…The decreased AID of fiber observed in our experiment may be due to increased mucin production, which can contaminate dietary fiber analyses. It has been determined that endogenous materials such as glycoproteins, microbes, and sloughed epithelial cells from the lumen of the gastrointestinal tract may be co-analyzed with dietary fiber when using the NDF, ADF, or TDF methods, resulting in an underestimation of dietary fiber digestion (Montoya et al, 2016). Mucins and bacteria are the primary endogenous materials that are included in and interfere with dietary fiber analyses when measured at the small intestine (Montoya et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The analytical methods used to measure dietary fiber were developed for the measurement of fiber in food products, but have been used by nutritionists for fiber measurements in ileal digesta and fecal samples in order to calculate fiber digestibility (Montoya et al, 2016). Previous reports of negative fiber digestibility values in monogastric animals, which are not physiologically possible, have called into question the accuracy of these methods when measuring dietary fiber in non-food materials (Wilfart et al, 2007;Cervantes-Pahm et al, 2014b).…”
Section: Analytical Methods For Measuring Dietary Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…Those results support those reported by Bach Knudsen et al [18], who found that the apparent ileal digestibility (AID) of NSP, which is the difference between TDF and lignin, in pigs, ranged from −7% to 40%. Importantly, some studies have reported that both the gastrointestinal digesta and the feces contain a significant amount of endogenous fibrous components from nondietary materials that interfere with the determination of dietary fiber fermentation [19,20]. The fermentation capacity of dietary fiber that is not corrected for the endogenous loss of fiber components can greatly underestimate dietary fiber fermentation.…”
Section: Discussionmentioning
confidence: 99%